(untitled) (Historia, 2021)
This article was prompted by the question of what had happened to women’s history from 1990. At that time, according to an assessment by Bozzoli and Delius, it had not (yet) developed into a “recognisable separate field of scholarship in South Africa”. The aim of this investigation is to explore the ways in which two collections of essays that appeared from 1990 onwards interpret the task of writing women’s history: Women and Gender in Southern Africa to 1945, edited by Cherryl Walker and published in 1990 and Women in South African History, edited by Nomboniso Gasa and published in 2007. While these collections of essays are by no means the only post-1990 publications with a focus on women’s and gender history, few others claim the same comprehensiveness in their titles. This study attempts to show how these two books functioned in the process of interpreting women’s history and whether or not each contributed to configuring the remit and the subject of South African women’s history and its status as a separate field. The agency (will power / instrumentality) required to produce and promote the books, the approaches taken in the two collections and the ways the former influenced the latter, will be investigated. This is done by tracing the reception of the two books in scholarly publications (with reference to book reviews as well as citations), and also by interviewing academics invested in the field.